The effects of self‐brand connections on responses to brand failure: A new look at the consumer–brand relationship - Cheng, Shirley Y.Y.; White, Tiffany Barnett; Chaplin, Lan Nguyen (Journal of Consumer Psychology, 2012)
AbstractWe argue that consumers with high self‐brand connections (SBC) respond to negative brand information as they do to personal failure — they experience a threat to their positive self‐view. After viewing negative brand information, high (vs. low) SBC consumers reported lower state self‐esteem. Consumers with high SBC also maintained favorable brand evaluations despite negative brand information. However, when they completed an unrelated self‐affirmation task, they lowered their brand evaluations the same as low SBC consumers. This finding suggests that high SBC consumers' reluctance to lower brand evaluation might be driven by a motivation to protect the self rather than the brand.